Effectiveness of the therapeutic program of ilioposoas and its effect on pelvic and lumbar stability - D. , Hossam Darwish Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Studies have shown that individuals with low back pain experienced a decrease in the strength of the ilioposoas muscle due to its connection to the pelvis and lumbar region. Because of this connection, the ilioposoas a muscle can stabilize the spine. In addition, where the pain occurs. Methods: A sample was chosen of a patient suffering from pain in the ilioposoas muscle and a back slope of the spine in the form of one group of (15). The primary measurements, such as height, weight, and age, are taken in addition to basic measurements such as angle of pelvic tilt, flexibility, muscularity, and posterior muscle length.Objective: The aim of this research is to identify the effect of the proposed rehabilitation exercises on the restoration of the basic functions of the lumbar region and the ilioposoas, a muscle, through the disappearance of pain. Restoring the motor range of the pelvic joint. The speed, muscle strength, and normal length restore the lumbar region of the spine to its natural state.Results: The proposed treatment program has a better effect on the return of the injured to a normal state.Restoring pain, strength, and elasticity; improving the motor range of the pelvic joint; returning the lumbar region to its natural position; and restoring the posterior muscle's elasticity. Recommendation: -We need to follow the physical mutations genetically in the family members periodically.Note the shape and extent of the joints during the performance of excessive flexibility in some joints.Strengthening the muscles in the region of the abdomen and pelvis, especially the muscle ilioposoas, with high follow-up instructions and abdominal exercise.The habits of being faulty and unstable in physical conditions for long periods and paying attention when shifting from the horizontal position of the head.